Latest Developments in Haptics Technology - Seema; Saini, Jasbir Singh; Kumar, Sanjeev (International Journal of Psychosocial Rehabilitation, 2020)
Haptic Technology has been discussed and also applied in industry in all domains. This paper reviews the latest in the field over the last three years. The technology starts with basics of touch, tactile and vicrotactile methods with the first task of grasp, in general, be it any application. Various hand-wearable devices with various combinations of techniques and devices have been used along with haptics till date. Many of these have been discussed in the paper. Also, we have tried to club similar work at one place chronologically to see the progress in the similar area over good labs worldwide, through peer-reviewed research papers. The paper aims at exploring the wide success accomplished in haptic technology and interfacing through various permutation combinations at different levels of device manufacture, especially in medical domain.